Prion strains viewed through the lens of cryo-EM - Szymon W. Manka; Adam Wenborn; John Collinge; Jonathan D. F. Wadsworth (Cell and Tissue Research, 2023)
Mammalian prions are lethal transmissible pathogens that cause fatal neurodegenerative diseases in humans and animals. They consist of fibrils of misfolded, host-encoded prion protein (PrP) which propagate through templated protein polymerisation. Prion strains produce distinct clinicopathological phenotypes in the same host and appear to be encoded by distinct misfolded PrP conformations and assembly states. Despite fundamental advances in our understanding of prion biology, key knowledge gaps remain. These include precise delineation of prion replication mechanisms, detailed explanation of the molecular basis of prion strains and inter-species transmission barriers, and the structural definition of neurotoxic PrP species. Central to addressing these questions is the determination of prion structure. While high-resolution definition of ex vivo prion fibrils once seemed unlikely, recent advances in cryo-electron microscopy (cryo-EM) and computational methods for 3D reconstruction of amyloids have now made this possible. Recently, near-atomic resolution structures of highly infectious, ex vivo prion fibrils from hamster 263K and mouse RML prion strains were reported. The fibrils have a comparable parallel in-register intermolecular β-sheet (PIRIBS) architecture that now provides a structural foundation for understanding prion strain diversity in mammals. Here, we review these new findings and discuss directions for future research.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Shadoo (Sprn) and prion disease incubation time in mice - Sarah E. Lloyd; Julia Grizenkova; Hirva Pota; John Collinge (Mammalian Genome, 2009)

Identification and characterization of a novel mouse prion gene allele - Sarah E. Lloyd; Simon R. Thompson; Jonathan A. Beck; Jacqueline M. Linehan; Jonathan D. F. Wadsworth; Sebastian Brandner; John Collinge; Elizabeth M. C. Fisher (Mammalian Genome, 2004)

Prion Diseases - Edward McKintosh; Sarah J Tabrizi; John Collinge (Journal of NeuroVirology, 2003)

Genomic characterization of the human prion protein (PrP) gene locus - Eleni Makrinou; John Collinge; Michael Antoniou (Mammalian Genome, 2002)

Prions and the prion disorders - Elizabeth Fisher; Glenn Telling; John Collinge (Mammalian Genome, 1998)